Financial Management / The Complete Course Text: 6th Edition - Brockington Raymond B (Dp Publications Ltd, 1993)
This book gives a full coverage of the subject of financial management to the level required by students taking the subject to a professionally qualifying level. Preface, Introduction, Funds Flow Statements, Sources of Finance, Financial Institutions, Cost of Capital, Capital Structure, Relevant Costs, Forecasting and Planning, Capital Budgeting, Risk, Capital Asset Pricing Model, Capital Rationing, Inflation and Financial Reporting, Inflation and Investment Appraisal, Taxation in Financial Decisions, Distribution Policy, Financial Ratios, Stock Market Investment, Mergers and Take-Overs, Management of Working Capital: Stock, Management of Working Capital: Debtors, Management of Working Capital: Cash Budgets, Foreign Currency Transactions, Appendices, Index.